2019
DOI: 10.1111/zph.12653
|View full text |Cite
|
Sign up to set email alerts
|

Comparable stx2a expression and phage production levels between Shiga toxin‐producing Escherichia coli strains from human and bovine origin

Abstract: Shiga toxin‐producing Escherichia coli (STEC) can cause diarrhoea and severe diseases in humans, such as haemolytic uraemic syndrome. STEC virulence is considered to correlate with the amount of Shiga toxins (Stx) produced, especially Stx2, whose subtype Stx2a is most frequently associated with high virulence. Stx are encoded in prophages, which play an important role in STEC pathogenesis. The aim of this study was to evaluate stx2a expression levels and Stx2a phage production using qPCR and the double‐agar‐la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The conserved genome localization of nan S-p suggests that its transcription is regulated by Q protein and prompted us to evaluate its expression under basal and mitomycin C-induced conditions in a set of stx 2a -positive STEC strains of our collection. The assays showed that all cultures, except one, increased nan S-p expression under induced conditions similar to that obtained for stx 2a in a previous study [37] . Furthermore, the exception was a strain that did not show nan S-p expression but had not demonstrated stx 2a expression either.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The conserved genome localization of nan S-p suggests that its transcription is regulated by Q protein and prompted us to evaluate its expression under basal and mitomycin C-induced conditions in a set of stx 2a -positive STEC strains of our collection. The assays showed that all cultures, except one, increased nan S-p expression under induced conditions similar to that obtained for stx 2a in a previous study [37] . Furthermore, the exception was a strain that did not show nan S-p expression but had not demonstrated stx 2a expression either.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have identified Q gene variants, of which Q 933 , Q 21 and Q O111:H- are the best characterized [48] . However, associations between each Q allele and levels of Stx2 production are still not clear [37] , [49] [51] . The present study detected stx 2a genes mainly linked to genes encoding proteins Q933 and QO111:H-, and none with Q21, similar to a previous study [50] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation